Applications of NMR spectroscopy. Volume 2 - Rahman, Atta-ur-; Choudhary, M. Iqbal (Sharjah, United Arab Emirates : Bentham Science Publishers Ltd., 2015)
Applications of NMR Spectroscopy, Volume 2, originally published by Bentham and now distributed by Elsevier, presents the latest developments in the field of NMR spectroscopy, including the analysis of plant polyphenols, the role of NMR spectroscopy in neuroradiology, NMR-based sensors, studies on protein and nucleic acid structure and function, and mathematical formations for NMR spectroscopy in structural biology. The fully illustrated chapters contain comprehensive references to the recent literature. The applications presented cover a wide range of the field, such as drug development, medical imaging and diagnostics, food science, mining, petrochemical, process control, materials science, and chemical engineering, making this resource a multi-disciplinary reference with broad applications. The content is ideal for readers who are seeking reviews and updates, as it consolidates scientific articles of a diverse nature into a single volume. Sections are organized based on disciplines, such as food science and medical diagnostics. Each chapter is written by eminent experts in the field.
''Cover'';''Title'';''EUL'';''Contents'';''Preface'';''List of contributor'';''Section A'';''Chapter 01'';''Section B'';''Chapter 02'';''Chapter 03'';''Section C'';''Chapter 04'';''Chapter 05'';''Index'';''Back Cover''
'Bentham E-Books'--Cover.
Includes bibliographical references at the end of each chapters and index.
Print version record.
Elsevier
Keywords: Nuclear magnetic resonance spectroscopy; SCIENCE / Chemistry / Analytic; Nuclear magnetic resonance spectroscopy; Electronic books; Electronic books